Firetrucks - Brady, Peter (Mankato, Minn : Bridgestone Books, 1996)
An introduction to fire trucks, what they carry, and what they do.
Includes bibliographical references (p. 24) and index.
72658
Keywords: Fire engines -- Juvenile literature; Fire engines